The adaptation of the Camagüey press to the Cuban historical change (1899-1935) - Adán Castaños, Yeni Yeisi (2025)
This article presents a preliminary exploration of the history of periodical publications that emerged in the city of Camagüey between 1899 and 1935, a period marked by significant sociopolitical, economic, cultural, and communicational transformations. The main objective is to analyse the chronological development ofthese local publications within the chosen timeframe, to understand their characteristics and adaptability to the new context. Using a qualitative and descriptive approach, the study employed historical-logical and analytical-synthetic methods at the theoretical level, complemented by bibliographic and documentary analysis at the empirical level. Data triangulation was used as the primary technique. The research examined a broad corpus of 19 periodicals with varying degrees of depth. Notable among the results is the study’s contribution to updating research on the history of the Cuban press and, in turn, to the corpus of scholarship on Camagüey’s local press; it also promotes the circulation and accessibility of the recovered archival materials.